Serial biomechanical comparison of edematous, normal, and collagen crosslinked human donor corneas using optical coherence elastography - Ford, Matthew R. (2014)
PURPOSE: To noninvasively evaluate the effects of corneal hydration and collagen crosslinking (CXL) on the mechanical behavior of the cornea. SETTING: Cleveland Clinic Cole Eye Institute, Cleveland, Ohio, USA. DESIGN: Experimental study. METHODS: An optical coherence elastography (OCE) technique was used to measure the displacement behavior of 5 pairs of debrided human donor globes in 3 serial states as follows: edematous, normal thickness, and after riboflavin–ultraviolet-A–mediated CXL. During micromotor-controlled axial displacements with a curved goniolens at physiologic intraocular pressure (IOP), serial optical coherence tomography scans were obtained to allow high-resolution intrastromal speckle tracking and displacement measurements over the central 4.0 mm of the cornea. RESULTS: With no imposed increase in IOP, the mean lateral to imposed axial displacement ratios were 0.035 μm/μm ± 0.037 (SD) in edematous corneas, 0.021 ± 0.02 μm/μm in normal thickness corneas, and 0.014 ± 0.009 μm/μm in post-CXL corneas. The differences were statistically significant (P<.05, analysis of variance) and indicated a 40% increase in lateral stromal resistance with deturgescence and a further 33% mean increase in relative stiffness with CXL. CONCLUSIONS: Serial perturbations of the corneal hydration state and CXL had significant effects on corneal biomechanical behavior. With an axially applied stress from a nonapplanating contact lens, displacements along the direction of the collagen lamellae were 2 orders of magnitude lower than axial deformations. These experiments show the ability of OCE to quantify clinically relevant mechanical property differences under physiologic conditions. FINANCIAL DISCLOSURES: Proprietary or commercial disclosures are listed after the references.